Influence of High RAP Content with Different Types of Fillers on HMA Resistance for Moisture Damage for Different Layers - Malik, Zainab; Abed, Alaa Hussen (Al-Nahrain Journal for Engineering Sciences, 2024)
Hot mix asphalt embedded on "Reclaimed asphalt pavement"(RAP) has the advantages of high technology. Moisture damage is a concern in these mixtures at all service temperatures. Therefore, the performance of this mixture against moisture at all service temperatures was considered a target of this research study. In this way, the effects of humidity on the performance of varieties were investigated using experimental methods including tensile strength ratio (TSR). In the framework of this study, Four different ratios of RAP for each of the surface and bonding layers (10%, 15%, 20%, 25%) and (30,40,50,60)% were added to the hot asphalt mix (HMA) for the two layers respectively to study and find the content Optimal RAP for both layers RAP through Marshall stability and hygroscopic resistance of asphalt mixtures through moisture damage is examined. The ratio (TSR) of the mixtures containing the optimal RAP content is compared with the asphalt mixture without RAP for three fillers and for both layers. The results showed a slight decrease in the tensile strength of the (HMA) that does not contain RAP compared to the asphalt control mixtures containing the reclaimed pavement, where it was found that the percentages were slightly higher and still higher than 80%. The results indicate that in general, Although there are old materials in the hot asphalt mix (HMA) produced from RAP, which include aggregates and bitumen binder surrounding the aggregate particles, the performance of these mixtures and integrations against moisture damage. Because it contains this, it can have results with “hot asphalt mixtures” containing RAP for areas with damage without worry in addition to good natural curbs.